Kualanamu Art Gallery & Exhibition Center (Structure as Elements of Aesthetics) - Samsul Bahri; Febby Khafilwara (International Journal of Architecture and Urbanism, 2018)
Medan is the third largest city in Indonesia, so it has considerable potential in the field of Art. A lot of potential and human resources that could be developed in the city of Medan. The city characterized by the culture of various Ethnic this hope was able to preserve the culture of each ethnic group. Art galleries and exhibition is expected to become a new tourism venue in the city of Medan and the iconic place of the development of works of art in the city of Medan. With the approach of the structure as elements of aesthetic in architecture